2017
DOI: 10.4172/2167-1044.1000269
|View full text |Cite
|
Sign up to set email alerts
|

Can Plasma Level of 3-methoxy-4-hydroxyphenylglycol Predict the Response for Selective Serotonin Reuptake Inhibitor and Serotonin Noradrenaline Reuptake Inhibitor in Major Depressive Disorder?

Abstract: IntroductionDepression is a serious mental illness requiring treatment. Major depressive disorder (MDD) is a complex disorder confounded by many bio psychosocial factors. Treatment with selective serotonin reuptake inhibitors (SSRIs) or serotonin noradrenaline reuptake inhibitors (SNRIs) is useful for MDD. The treatment of MDD requires collaborative efforts and holistic approaches by healthcare providers, public health interventions, and a reform in policies as well as the allocation of resources for the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Altogether, this previous study helped to understand the fact that norepinephrine levels play an etiological role in mood disorders. These data revealed that depression exists in two forms-a norepinephrine depression, marked by low levels of MHPG 10 and another, a serotonin depression 11 marked by the high levels of MHPG.…”
Section: Norepinephrinementioning
confidence: 92%
“…Altogether, this previous study helped to understand the fact that norepinephrine levels play an etiological role in mood disorders. These data revealed that depression exists in two forms-a norepinephrine depression, marked by low levels of MHPG 10 and another, a serotonin depression 11 marked by the high levels of MHPG.…”
Section: Norepinephrinementioning
confidence: 92%